The Different Time Administration of Cherry Leaf Teabag (Muntingia calabura L.) to Broiler Immunity - Mawarni, I; Putri, D D; Candra, A A; Noviadi, R; Maradon, G G (Politeknik Negeri Lampung, 2024)
This study purpose was to analyze the different time administration of cherry leaf teabag (Muntingia calabura L.) to broiler immunity. This study used 2 treatment groups. The first group (T1) was given cherry leaf teabag (Muntingia calabura L.) every day in drinking water (T1), and the second group (T2) was given cherry leaf teabag (Muntingia calabura L.) every two days. The dosage of cherry leaf used in this study 420 mg/kg BW. Paired samples t-test was used to compare the results of the two treatment groups. To determine the effect of different time administration of cherry leaf teabag on the broiler immunity, the parameter observed was the antibody titer in response to Newcastle Disease vaccination, another parameter observed is the weight percentage of the lymphoid organs (Bursa of Fabricius and Spleen) to find out that the herbs with immunostimulatory activity do not cause lymphoid organs to work excessively does not cause the lymphoid organs to work excessively. Based on the results of this study, it was concluded that giving Cherry leaf teabag (Muntingia calabura L) every two days had almost the same effect in increasing broiler immunity as giving every day, and giving Cherry leaf teabag (Muntingia calabura L) every day also does not have a negative effect on the lymphoid organs which are responsible for immunity